Identification of Prognostic and Predictive Markers in Pancreatic Adenocarcinoma - Russo, Suzanne M; Ove, Roger; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Pancreatic cancer remains a significant cause of morbidity and mortality. While increasing treatment options have improved outcomes for many patients, they have also complicated decision-making for treatment. Unfortunately, most patients with pancreatic cancer die from their disease. Prognostic and predictive markers could play a role to improve treatment by identifying patients who may or may not require a given therapy, and determining those most likely to benefit from a therapy. At the 2011 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium held in San Francisco, January 2011, several interesting abstracts were presented that focused on prognostic and predictive markers associated with pancreatic adenocarcinomas. These abstracts discuss progress made in identifying molecular subtypes of pancreatic cancers that may provide insight into selection of patients likely to benefit from certain therapies. Image: Mitchell Cancer Institute, University of South Alabama. Mobile, AL, USA.